Indonesian Coffee Exports' Competitiveness and Determinants - Purwawangsa, Handian; Irfany, Mohammad iqbal; Haq, Daffa Aqomal (School of Business, Bogor Agricultural University (SB-IPB), 2024)
This study assesses the competitiveness of Indonesian coffee in relation to its primary global competitors - Brazil, Colombia, and Vietnam. Focusing on key export markets, including the United States, Japan, and Egypt, the research analyses factors influencing the demand for coffee exports. The study utilizes time series data (2004-2021) of coffee under HS code 090111 and applies Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and the Linear Approximate Almost Ideal Demand System (LA-AIDS). Findings highlight Indonesian coffee's lower competitiveness, with Vietnam emerging as the top competitor. Additionally, demand determinants for Indonesian coffee have a smaller impact compared to those from other nations. Notably, Indonesian coffee exhibits price inelasticity in the U.S. market and high elasticity in Egypt. The study suggests strategies to improve competitiveness such as quality enhancement, product diversification, market access expansion through certification, and farmer capacity building to mitigate quality issues from green-picking practices. Keywords: Indonesian coffee, coffee competitiveness, RCA, EPD, LA-AIDS